Politeness in student-lecturer whatsapp messages: A study of English greetings - Jaya, Patria Handung; Wijana, I Dewa Putu; Hardjanto, Tofan Dwi (Universitas Ahmad Dahlan, 2025)
WhatsApp is an option for communicating in the current era, regardless people’s background. In the world of education, for instance, both students and lecturers also use this application for teaching and learning activities. Unfortunately, not many students communicate with this media properly so the messages sent to their lecturers tend to be impolite, especially when the messages are sent in English. One indicator of this is the absence of greetings in the message. None of the previous research has discussed the specific element(s) of a message that becomes the gap of this research. This research aims to find out what greetings students usually use when sending English messages to lecturers and how important greetings are in sending a text message. This quantitative research involved 60 lecturers who teach in English Department or teach English subjects throughout Indonesia who filled out questionnaires and expressed their opinions on several English text messages sent by students. The result shows that there are several types of greetings used by students, such as